PWE-048 The virtual electronic chromoendoscopy score in ulcerative colitis exhibits very good inter-rater agreement in scoring mucosal and vascular changes after computerised module training: a study across academic and community practice. (17th June 2017) - Trivedi, P; Ghosh, S; Iacucci, M; ,; J, Hodson; N, Bhala; R, Cooney; R, Boulton; X, Gui; T, Iqbal; K-k, Li; S, Mumtaz; et al.
Abstract : Introduction: Mucosal healing is the desired therapeutic endpoint for clinical trials in ulcerative colitis (UC). However, conventional white light endoscopy may fall short of capturing the full spectrum of inflammatory change; and virtual electronic chromoendoscopy (VEC) can show ongoing disease activity even when Mayo scores suggest healing (Iacucci et al. Endoscopy 2015 and 2017). Applicability of VEC scoring requires determination outside the expert setting; thus, our aim was to provide external validation among trainees, consultant gastroenterologists and colorectal surgeons, practicing across six general and specialist centres. Method: 15 participants reviewed a computerised training module outlining HD and i-Scan modes. Anchor points for the VEC score indicated mucosal changes (crypt distortion, 0 [A–C]; microerosions, I [1–3]; erosions, II [1–3]; and ulceration, III [1–3]) and vascular alterations (non-dilated vessels, 0 [A–C]; dilated/crowded vessels, I [1–3]; mucosal bleeding, II [1–3]; and intraluminal bleeding, III [1–3]). Performance accuracy was tested using a video library pre-/post-training (n=30). Agreement between raters was tested for the Mayo score, UCEIS and VEC score, and results correlated with histology (New York Mount Sinai system). Results: The inter-rater agreement was very good for the Mayo score, UCEIS scoring erosions/ulcers and overall, and for VEC scoring mucosal patterns in both modules (Table 1). For the vascular components of UCEIS agreement was only moderate, and did not improve post-training; unlike the agreement for VEC vascular patterns which improved significantly to very good. Correlation between histology and VEC score was highly significant for mucosal and vascular scoring (Spearman's ρ: 0.910, p<0.001; and 0.907, p<0.001; respectively, Figure 1). This was superior to the Mayo score (0.876, p<0.001) and UCEIS (0.887, p<0.001). Conclusion: The VEC score demonstrates very good inter-observer agreement across all levels of experience and provides excellent correlation with histology. Unlike UCEIS, the VEC score does not have subjective elements (e.g. mucosal erythema, incidental/contact friability) and may better delineate vascular changes due to filter technology. Given the ability to define subtle endoscopic features, VEC may be applied to further stratify treatment paradigms for patients with UC. Disclosure of Interest: P. Trivedi Conflict with: Received funding from the National Institute for Health Research (NIHR), Conflict with: This article presents independent research funded by the NIHR. The views expressed are those of the authors and not necessarily those of the NHS, the NIHR or the Department of Health, S Ghosh: None Declared, M Iacucci: None Declared